(NwWEDENIE W KALIBROWO^NU@ POLEWU@ TEORI@ \LEKTROSLABYH WZAIMODEJSTWIJ (B/s - (NbOGU[(B, (NaNDREJ aLEKSANDROWI^s ((NmINSK (B:s (NnAUKA I TEHNIKA(B,s, 1987)
(NbIBLIOGR(B.: (NS(B. 349-354 (150 (NNAZW(B.)s
(NpREDM(B. (NUKAZ(B.: (NS(B. 355-359s
(Nan bssr(B, (NiN(B-(NT FIZIKIs
Keywords: (NkWANTOWAQ TEORIQ POLEJs